The woodwasp genus Tremex (Hymenoptera, Siricidae) of Japan - Shinohara, Akihiko (Zootaxa, 2023)
The woodwasp genus Tremex Jurine, 1807, is revised for Japan and eight species are recognized, T. apicalis Matsumura, 1912, T. bicinctus Shinohara, n. sp., T. contractus Maa, 1949, T. fuscicornis (Fabricius, 1787), T. katayamai Shinohara & Kurihara, n. sp., T. longicollis Konow, 1896, T. nakanei Takeuchi, 1955, and T. okinawensis Togashi, 1997. Tremex bicinctus is described from Honshu and Kyushu and T. katayamai is described from Honshu, both based only on females. Tremex kaedei Togashi, 1997, is a new synonym of T. nakanei Takeuchi, 1955, and T. kurokivorus Togashi, 2006, is a new synonym of T. okinawensis Togashi, 1997. Tremex sudajii Togashi, 2006, is transferred to the genus Eriotremex Benson, 1943. Tremex okinawensis is newly recorded from Amami-ôshima Island and the male of this species is diagnosed for the first time. Pterocarya rhoifolia (Juglandaceae) is newly recorded as a host plant of T. nakanei. Keys are given for the females of eight Japanese species and for the males of six Japanese species. The stability and taxonomic use of some characters, mostly employed in previous works, are examined and discussed. Collection records are given for 443 specimens of eight species examined.